Financing Education in Developing Countries: Philanthropic Organizations need to monitor their investment for impact - Raymond Saner; Lichia Yiu (University of Basel, Center for Philanthropy Studies (CEPS), 2019)
Philanthropic organisations (PO) are important partners in the context of the Sustainable Development Goals (SDGs) and in regard to capacity building for education in Developing Countries (DCs) especially regarding Goal 4 education and Goal 17 partnerships. The POs contributions in DCs are important but their own strategic intent and the development impact of their local partners in the DC needs to be better understood to ensure mutually successful cooperation. This paper sheds light on the various contextual differences that might make a PO's investment difficult. For instance, a DC's strategic intent in terms of cooperation with POs is to ensure the development of a productive workforce, responsible citizens and to improve the country's deficits of its educational sector. A PO investing in education in a DC might have convergent and divergent objectives, which need to be addressed in order to avoid conflicts with the DC and possible premature ending of their cooperation. This paper discusses the constraints and opportunities of providing educational services across borders. It makes reference to hurdles that need to be identified and appropriately addressed such as rules regarding trade in education services as defined by WTO agreements as well as other national rules which a PO investor needs to know, respect and manage such as labour rules covering teaching faculty, educational fees and scholarly grading systems. Investing by providing education to a DC can be successful under the condition that the PO develops and applies a comprehensive monitoring system that helps the PO understand and constructively manage the investment challenges at Meta, Macro, Meso and Micro level. This paper explains the different levels and provides suggestions how these multiple hurdles can successfully be overcome for the benefits of all parties involved in cross-border educational investment by a non-state actor (PO) in a developing country.
Keywords: 330; Philanthropic Organisations; Investment in education in Developing Countries; Monitoring investment; State versus Non-State actor cooperation